ANALYSING PUBLIC PERCEPTION OF WOMEN’S POLITICAL PARTICIPATION IN NIGERIA - Nwagwu, Christian Nwabueze; Iwuala, Caleb Chukwuebuka; Ebeh, Richards E. (African Journal of Social and Behavioural Sciences, 2024)
This study investigated the public perception of women’s political participation in Nigeria, with emphasis on analysing the relationship between the belief that women lack the requisite education and skills for political engagement and the general public’s opinion of women’s participation in politics. The research population consisted of 240 Nigerian citizens selected through the convenience sampling technique. The study employed a descriptive design approach where participants were administered a self-reported questionnaire. Descriptive statistics and the Spearman Correlation Coefficient were used to analyse data collected using the Statistical Packages for Social Sciences (SPSS, Version 27) The results indicated that the majority of the participants believed that women have the training and skills necessary to completely participate in politics. In addition, the findings demonstrated the positive influence of Nigerian public opinion on women’s political participation. This perception, however, creates a considerable barrier, restricting women’s participation in the political process and limiting their representation. Several factors that influence public perception include socioeconomic status, educational background, and cultural norms. There were also demographic differences in public opinion based on gender, age, and level of education. Based on the study’s findings, the study recommends education and awareness initiatives, leadership development programmes, gender-sensitive legislation, establishment of women’s support networks and institutions and promoting a commitment to gender equality in politics. The study concluded that these may assist in dispelling misconceptions, increasing women’s political participation, and fostering a more inclusive and representative democracy in Nigeria.